2022
DOI: 10.1136/jim-2022-002334
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction and Concomitant Acute Intracranial Hemorrhage: Clinical Characteristics and Outcomes

Abstract: This study aimed to evaluate the demographic and clinical characteristics, treatments and outcomes of concomitant acute myocardial infarction (AMI) and acute intracranial hemorrhage (ICH). All patients diagnosed with concomitant AMI and acute ICH admitted to our institution were included retrospectively. The patient demographics, clinical characteristics, neuroimaging and treatment approaches were analyzed, and the outcomes of interest included disability as defined by the modified Rankin Scale (mRS) score and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The study conducted by Cao et al highlights that the decision to treat acute MI or acute intracerebral hemorrhage first depends on the patient's hemodynamic stability. Cardiac catheterization may be performed without antithrombotic or antiplatelet use in cases of hemodynamic instability or STEMI after acute intracerebral hemorrhage [12]. Patlolla et al reported that most patients with acute MI with intracranial hemorrhage less often required coronary angiography, percutaneous coronary intervention, or coronary artery bypass grafting as compared to those without intracranial hemorrhage [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by Cao et al highlights that the decision to treat acute MI or acute intracerebral hemorrhage first depends on the patient's hemodynamic stability. Cardiac catheterization may be performed without antithrombotic or antiplatelet use in cases of hemodynamic instability or STEMI after acute intracerebral hemorrhage [12]. Patlolla et al reported that most patients with acute MI with intracranial hemorrhage less often required coronary angiography, percutaneous coronary intervention, or coronary artery bypass grafting as compared to those without intracranial hemorrhage [13].…”
Section: Discussionmentioning
confidence: 99%
“…The confluence of TBI and MI introduces uncertainties in predicting both neurological and cardiovascular outcomes. According to Cao et al, 50% of patients with concomitant acute STEMI and acute intracerebral hemorrhage have poor prognosis [12]. Prognostication becomes challenging, and the long-term impact on the patient's quality of life requires careful consideration.…”
Section: Discussionmentioning
confidence: 99%